Are Healthcare Expenditures Related to Economic Growth in China? Bootstrap ARDL Approach - Chang, Yu-Cheng; Chang, Tsangyao; Wang, Mei-Chih (Frontiers in Public Health, 2022)
This study attempts to investigate whether health care expenditures are related to economic growth in China using a newly developed Bootstrap ARDL bound test for China over the period of 1990 to 2019. To avoid omitted variable bias we use the ratio of the population of 65 years old over total population (aging ratio) as a control variable. Empirical result indicates that no cointegration among these three variables. Granger causality test based on Bootstrap ARDL model demonstrates that one-way Granger causality running from health care expenditures to aging ratio and from economic growth to both health care expenditures and aging ratio. Empirical results have important policy implications for China understudy